Election process in the era of information technologies (foreign experience of legislative regulation) - Kandratovich, Natallia М. (Journal of the Belarusian State University. Law, 2025)
The article deals with the legislative basis and practice of application of modern information technologies in conducting elections in some foreign countries. The procedural peculiarities of information technologies usage in the practice of holding elections in some countries of the world are characterised.
Keywords: election process; stages of election process; electronic election system; electronic collection of signatures; electronic voting; dipfakes; artificial intelligence